2022
DOI: 10.1080/14686996.2022.2149034
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate) scaffolds – a step towards ligament repair applications

Abstract: The incidence of anterior cruciate ligament (ACL) ruptures is approximately 50 per 100,000 people. ACL rupture repair methods that offer better biomechanics have the potential to reduce long term osteoarthritis. To improve ACL regeneration biomechanically similar, biocompatible and biodegradable tissue scaffolds are required. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), with high 3-hydroxyvalerate (3HV) content, based scaffold materials have been developed, with the advantages of traditional tissue eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The results showed good cellular viability. They concluded that the aligned fibers network promotes fibroblast alignment in the axial fiber direction, which is desirable for ACL repair applications [84].…”
Section: Phbv Composites For Tissue Engineering Applicationsmentioning
confidence: 99%
“…The results showed good cellular viability. They concluded that the aligned fibers network promotes fibroblast alignment in the axial fiber direction, which is desirable for ACL repair applications [84].…”
Section: Phbv Composites For Tissue Engineering Applicationsmentioning
confidence: 99%